Effect of Hydrogen Peroxide on the Biosynthesis of Heme and Proteins: Potential Implications for the Partitioning of Glu-Trnaglu Between These Pathways - Levican-Jaque, G (Multidisciplinary Digital Publishing Institute (MDPI), 2014)
Glutamyl-tRNA (Glu-tRNAGlu) is the common substrate for both protein translation and heme biosynthesis via the C5 pathway. Under normal conditions, an adequate supply of this aminoacyl-tRNA is available to both pathways. However, under certain circumstances, Glu-tRNAGlu can become scarce, resulting in competition between the two pathways for this aminoacyl-tRNA. In Acidithiobacillus ferrooxidans, glutamyl-tRNA synthetase 1 (GluRS1) is the main enzyme that synthesizes Glu-tRNAGlu. Previous studies have shown that GluRS1 is inactivated in vitro by hydrogen peroxide (H2O2). This raises the question as to whether H2O2 negatively affects in vivo GluRS1 activity in A. ferrooxidans and whether Glu-tRNAGlu distribution between the heme and protein biosynthesis processes may be affected by these conditions. To address this issue, we measured GluRS1 activity. We determined that GluRS1 is inactivated when cells are exposed to H2O2, with a concomitant reduction in intracellular heme level. The effects  of H2O2 on the activity of purified glutamyl-tRNA reductase (GluTR), the key enzyme for heme biosynthesis, and on the elongation factor Tu (EF-Tu) were also measured. While exposing purified GluTR, the first enzyme of heme biosynthesis, to H2O2 resulted in its inactivation, the binding of glutamyl-tRNA to EF-Tu was not affected. Taken together, these data suggest that in A. ferrooxidans, the flow of glutamyl-tRNA is diverted from heme biosynthesis towards protein synthesis under oxidative stress conditions. © 2014 by the authors; licensee MDPI, Basel, Switzerland.